Biocatalytic oxidation of Arsenic (III) with concomitant Chromium (VI) reduction by an autotrophic culture of bacteria - Chirwa, Evans M.N. (University of Pretoria, 2019)
Thesis (PhD)--University of Pretoria, 2018.